WHAT CAN SLA LEARN FROM CONTRASTIVE CORPUS LINGUISTICS? THE CASE OF PASSIVE CONSTRUCTIONS IN CHINESE LEARNER ENGLISH - Richard Zhonghua Xiao (Universitas Katolik Indonesia Atma Jaya, 2007)
This article seeks to demonstrate the predictive and diagnostic power of the integrated approach that combines contrastive corpus linguistics with interlanguage analysis in second language acquisition research, via a case study of passive constructions in Chinese learner English. The type of corpora used in contrastive corpus linguistics is first discussed, which is followed by a summary of the findings from a published contrastive study of passive constructions in English and Chinese based on comparable corpora of the two languages. These findings are in turn used to predict and diagnose the performance of Chinese learners of English in their use of English passives as mirrored in a sizeable Chinese learner English corpus in comparison with a comparable native English corpus. Keywords: contrastive analysis, corpus, learner English, passive construction, Chinese